THE INFLUENCE OF LEVERAGE AND LIQUIDITY ON DIVIDEND POLICY (Empirical Study on Listed Companies in Indonesia Stock Exchange of LQ45 in 2008-2010) - Lalu Candra Karami, SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research is purposed to test the influence of current ratio and debt to equity ratio toward dividend policy which is proxy as dividend payout ratio to companies which are listed in LQ-45 at Indonesia Stock Exchange in the period of 2008-2010. This research applies purposive sampling technique with 15 samples of companies. Multiple regression is a technical analysis method applied. The result of t test partially indicates that leverage influences negatively and significantly towards dependent variable, which is dividend payout ratio. Liquidity gives positive and significant influence towards dividend policy. Actually, there are some classical assumption tests, such as normality test, multicollinearity test, homoscedasticity test, and autocorrelation test. Keywords : debt to equity ratio, current ratio, dividend payout ratio